Effect of Slam Waves Battle rope Exercise and Up down Waves Battle rope Exercise to Arm Strength And Arm Endurance (Study of boxing exstracurriculer at senior high school 3 Kediri) - Dhayu Briyan Wijaya; Wijono Wijono; Acmad Widodo (BIRCU, 2020)
The most popular extraculiler in kediri High School 3 is boxing, because it can be done and studied by both male and female students. Boxing extraction itself is in demand because it is a well-known sport with weight loss and also for self-defense. Boxing itself requires a hard punch produced from a strong arm and also requires the stability of the hand to be beside the face to support the punch technique that is in boxing.When observing at State High School 3 Kediri, many students had not yet mastered the physical condition of the arm muscle strength or arm muscle endurance. Extraculiler trainers and teachers also said that physical conditions and non-boring forms of training are important to improve student achievement in school and outside school performance. Based on the background description above, the researcher wants to provide alternative exercises to improve physical conditions specifically in increasing arm muscle strength and endurance of arm muscles in male and female extracurricular students of SMAN 3 Kediri. So that researchers are interested in conducting research